Dampak Sosial Ekonomi Tempat Pembuangan Akhir (TPA) Sampah Cipeucang Bagi Pemulung Sekitar - Fitria, Nada; Nisa, Jakiatin; Bahar, Syairul (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2024)
Cipeucang landfill has become a place where waste collects which has a direct impact on local scavengers. The proximity of the scavenger community's residential location in Serpong Subdistrict to the landfill site means that the scavenger community is vulnerable to coming into contact with waste. This research aims to determine the socio-economic impact of the Cipeucang waste final disposal site (TPA) on local scavengers. The method used in this research is a descriptive qualitative approach. with this type of phenomenological research. The object of this research is society. scavengers who are around the Cipeucang TPA and who are the subjects are the scavenger community of RT 06 RW 04 who live and are in direct contact with the TPA. The data collection technique used in this research was observation interviews. and documentation. The results of the analysis show that there are positive and negative impacts on the scavenger community around the Cipeucang landfill. Among them is the positive impact of the large number of local scavenger communities whose main income is from scavenger work with very varied incomes, where the income earned by the The negative impact is that the residences occupied by scavengers are still inadequate because the residences they occupy in terms of the physical condition of the building are still considered vulnerable to potential danger, apart from that, in terms of education among the scavenger community, it is still relatively low, because many of them are the children of scavengers. who dropped out of school again because of financial constraints.